Micropollutants cometabolism of microalgae for wastewater remediation: Effect of carbon sources to cometabolism and degradation products. (15th September 2020) - Vo, Hoang Nhat Phong; Ngo, Huu Hao; Guo, Wenshan; Nguyen, Khanh Hoang; Chang, Soon Woong; Nguyen, Dinh Duc; Liu, Yiwen; Liu, Yi; Ding, An; Bui, Xuan Thanh
Abstract: This study investigated the impacts of selective sole carbon source-induced micropollutants (MPs) cometabolism of Chlorella sp. by: (i) extracellular polymeric substances (EPS), superoxide dismutase and peroxidase enzyme production; (ii) MPs removal efficiency and cometabolism rate; (iii) MPs' potential degradation products identification; and (iv) degradation pathways and validation using the Eawag database to differentiate the cometabolism of Chlorella sp. with other microbes. Adding the sole carbon sources in the presence of MPs increased EPS and enzyme concentrations from 2 to 100-fold in comparison with only sole carbon sources. This confirmed that MPs cometabolism had occurred. The removal efficiencies of tetracycline, sulfamethoxazole, and bisphenol A ranged from 16-99%, 32–92%, and 58–99%, respectively. By increasing EPS and enzyme activity, the MPs concentrations accumulated in microalgae cells also fell 400-fold. The cometabolism process resulted in several degradation products of MPs. This study drew an insightful understanding of cometabolism for MPs remediation in wastewater. Based on the results, proper carbon sources for microalgae can be selected for practical applications to remediate MPs in wastewater while simultaneously recovering biomass for several industries and gaining revenue. Graphical abstract: Image 1 Highlights: EPS and enzyme concentrations increased 2 to 100 times while exposing to MPs. TC, SMX and BPA were removed 16–99%, 32–92% and 58–99%, respectively. MPs concentrations in microalgae cells decreased 400 times by cometabolism. metabolites of BPA were detected. A straight chain product (m/z 253) was found and did not exist in Eawag database.